Association Between Individual and Geographic Factors and Nonadherence to Mammography Screening Guidelines - Henry, Kevin A (Mary Ann Liebert, Inc., 2014)
Background: This study investigates factors that are associated with nonadherence to mammography screening guidelines in Utah, a state where mammography screening rates have remained consistently lower than national averages. Methods: We examined data on reported mammography use among women aged 40–74 years from the 2008 and 2010 Utah Behavioral Risk Factor Surveillance System (n=5,197, weighted n=417,064). Logistic regression models were used to estimate the effects of individual-level and geographic (travel time to nearest mammography facility, geographic accessibility, and rural/urban residence) factors on the odds of a woman not reporting receiving a mammogram in the last 2 years. Results: In 2008 and 2010, a disproportionate number of women aged 40–49 (43.1%, 95% confidence interval [CI] 39.9%–46.3%) reported not receiving a mammogram within the last 2 years compared to women 50–74 (26.8%, 95% CI 24.9%–28.7%). None of the geographic factors were significant predictors of screening adherence. Based on covariate adjusted models, statistically significant (p<0.05) factors associated with increased odds of not receiving mammogram within the last 2 years included not having a regular physician, no health insurance, being aged 40–49, income less than $25,000, and the presence of three or more children in the home. Conclusion: Mammography screening efforts in Utah should focus on improving access to insurance or a regular source of health care. Future research should also consider how best to address extreme time demands and competing priorities that present potential barriers for women with large families, resulting in lower screening levels among these women.